The Popularity of TikTok and the Implementation of the AISAS Model on Marketing Communications Through TikTok - Anggun Sari Sasmita; Nila Sartika Achmadi (Universitas muhammadiyah malang, 2022)
The development of social media use has increased during the Covid-19 pandemic. The existence of social like TikTok, it is hoped that it will be able to help entrepreneurs to continue their business. This study aims to find out what causes TikTok's popularity and how to implement the AISAS model in marketing communications through TikTok. Researchers chose literature review as a research method in this paper to look deeper into the phenomena that occur. The conclusion of this study shows that the popularity of TikTok is caused by fear of missing out, or the fear of missing the trend and not being able to engage in the conversations of people in the environment, the ease of downloading and sharing videos, the ease of using the application, interesting content and the opportunity to shorten the marketing funnel.